Perspectives on Neonatal Visits Coverage in Serdang Bedagai Regency Indonesia: A Qualitative - Novita Br Ginting Munthe; Rizanda Machmud; Rima Semiarty; Joserizal Serudji; Adang Bachtiar; Finny Fitry Yani; Denas Symond; Nelwati Nelwati (Indonesian Journal of Global Health Research, 2025)
The purpose of neonatal visits is to re-examine newborns, review counseling and anticipation guidelines with parents, identify symptoms of illness, and educate and support parents. The purpose of neonatal visits is to improve neonatal access to basic health services and to find out as early as possible if there are abnormalities in the baby or if there are problems. One important indicator to describe the level of public health is the infant mortality rate. Objective to find out more about the perspectives on neonatal visit coverage in Serdang Bedagai District, Indonesia. The study was a qualitative with phenomenology approach. Twenty-five informants were applied in this study using purposive sampling. Data were collected using in-depth interviews. Data were analyzed using content analysis by the collaizi method. The study emerged nine themes, namely: 1) knowledge about neonatal visits; 2) neonatal visit quantity standards; 3) neonatal visit quality standards; 4) health care workers providing neonatal visiting services; 5) purpose of neonatal visits; 6) relationship between education and neonatal visit compliance; 7) relationship between husband/family support and neonatal visit compliance; 8) reasons for non-compliance with neonatal visits; and 9) culture in support of public health. These results can be input for policymakers to increase the coverage of neonatal visits in Serdang Bedagai Regency, Indonesia.